Dari Radikal-Ekstrimis ke Moderat Islam: Membaca Pergeseran Faham Moderat pada Kelompok Mantan Teroris di Indonesia - Mujib Ridlwan (Al Hikmah: Jurnal Studi Keislaman, 2020)
Abstract: This article describes the change in attitude of former terrorists in Lamongan from the causes of being interested in being terrorists to returning from terrorists to individuals who have moderate attitudes. From the results of the study it can be explained that what causes the terrorists to be attracted to terrorism is influenced by friends, family, and people who are identified. His interest is because information that is under by friends, family, and people who characterize is attractive to potential terrorists or individuals who return from terrorists to be moderate. Information that turns individuals into terrorists, including, there is injustice in the hemisphere between Western countries and Muslims, there is a jih kewajiband obligation (fighting with weapons) to groups or people who harm Muslims. "Isy karȋman aw mut shahȋdan" (noble life or death shahid) is a choice. If you are unable to live, then Shahid dies. Such information is always echoed which leads individuals to become involved in becoming terrorists. Likewise terrorist individuals experience change to be moderate, because it is influenced by information, including the presence of victims or other parties who are harmed due to individual acts of terrorists. In addition, the basic human nature of wanting to be safe, comfortable, and peaceful is the reason for individual terrorists to change their attitude to be moderate. Keywords: change of attitude; terrorist; moderate.